A high temperature resistant and high lubricity coating for aviation fastener wire and its application
Through the combination of graphite, nanomolybdenum disulfide, molybdenum carbide and carbon black, a high-temperature and high-lubricating coating is formed, which solves the problem that the coating of titanium alloy fasteners is easy to peel off at high temperatures, and realizes the high-temperature environment Stable lubrication isolation effect, improving production efficiency and material protection.
Patent Information
- Application Number
- CN202310705395.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-14
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-06-14
AI Technical Summary
The coating of existing titanium alloy fasteners is prone to peel off under high temperature environments, and cannot maintain lubrication and isolation during continuous high temperature pier making, resulting in material damage and low production efficiency.
Use specific proportion combinations of graphite, nano-molybdenum disulfide, molybdenum carbide and carbon black to form a high-temperature resistant and high-lubricating coating, which is uniformly coated on the surface of the titanium alloy wire through electrostatic spraying technology to enhance the adhesion of the coating and Lubricating properties, inhibit oxidation and structural decay.
Good adhesion and lubricity are maintained in normal temperature and high temperature environments, preventing the coating from peeling and denaturation, ensuring smooth titanium alloy fasteners at high temperatures, and improving production stability and efficiency.
Smart Images

Figure BDA0004285783000000051 
Figure BDA0004285783000000071 
Figure HDA0004285783010000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium alloy processing materials, and in particular to a high-temperature resistant and high-lubricity coating for aviation fastener wire and an application thereof. Background Art
[0002] Fasteners are a type of mechanical parts that fasten two or more parts together and are known as the "rice of industry". Aerospace fasteners refer to fasteners used in aerospace and can meet the special technical requirements of aerospace. They are usually used in aerospace vehicles such as airplanes, satellites, and rockets. They are a typical high-end fastener with extremely high performance requirements.
[0003] Titanium and titanium alloy fasteners have the characteristics of light weight, high specific strength, good thermal strength, and high temperature resistance. They are increasingly used in aircraft, engines, and aerospace vehicles, and are widely used in modern aviation and aerospace industries. The preparation process of titanium alloy fasteners ranges from turning forming to single-pier forming to continuous pier forming. Continuous pier forming is becoming the main development direction of titanium alloy fastener production due to its advantages such as high material utilization and high pier efficiency. However, due to the high chemical activity and easy adhesion of titanium alloys, there are still many problems in actual production and use. The existing technology usually applies a lubricating coating on the surface of titanium alloys to achieve the effect of protecting materials, reducing friction, and facilitating piercing. However, there are still many problems in the use of existing lubricating coatings, such as easy peeling of the coating due to scratches at room temperature, and easy failure and shedding of the coating at high temperature; especially in the continuous high-temperature pier deformation process, the coating falls off too early, and the lubrication and isolation effect of the deformation process of multi-mode multi-punching such as three-mode six-punching cannot be completed.
[0004] How to form a good lubricant coating on the surface of titanium alloy wire, which is the raw material of fasteners, and effectively play a lubricating and isolating role in the continuous forging process has become a bottleneck in the continuous forging forming process of titanium alloy fasteners. In particular, Ti6Al4V titanium alloy fasteners require a high temperature environment of 700-820℃ to be successfully forged, and the lubricating coating is required to maintain firm adhesion in a high temperature environment and at the same time have a good lubricating and isolating effect. Summary of the invention
[0005] In view of the above problems, the present invention provides a high-temperature resistant and high-lubricity coating for aviation fastener wire. The coating has excellent adhesion at room temperature and can prevent the moving wire from scratching and causing the coating to peel off. In a high-temperature environment, the performance is maintained well and it is not easy to degenerate. It also has good adhesion and is not easy to fall off.
[0006] On one hand, the present invention provides a high-temperature resistant and high-lubricity coating for aviation fastener wire. The raw materials of the coating include, by weight, 20-30 parts of graphite, 30-40 parts of molybdenum disulfide, 3-10 parts of molybdenum carbide, 20-30 parts of silicate, 1-5 parts of silicon powder, and 15-30 parts of diluent.
[0007] Graphite belongs to the hexagonal layered crystal structure, the carbon atoms in the layer are connected by strong covalent bonds, and the carbon atoms between the layers are connected by weaker van der Waals forces. When subjected to shear forces in parallel directions, the layers are very easy to slide, so it has a lower friction coefficient and has good electrical conductivity, thermal conductivity and high temperature resistance. Molybdenum disulfide also belongs to the layered hexagonal metal chemical, its Mo and S atoms are connected by strong covalent bonds, and the molecular layers are connected by weaker van der Waals forces. The layers are also easy to slide, and have excellent lubrication properties, but molybdenum disulfide is easy to oxidize, especially in a humid environment, which leads to poor lubrication performance. Molybdenum carbide belongs to the hexagonal system, has good thermal stability, mechanical stability and other properties, and the lubricating coating of the present invention uses several components in combination, and has excellent high temperature resistance and lubrication effects.
[0008] Preferably, the average particle size of the graphite is less than 3 μm, and the specific surface area is 10-50 m 2 / g.
[0009] Preferably, the molybdenum disulfide is nano molybdenum disulfide.
[0010] Preferably, the raw materials for preparing molybdenum disulfide include: ammonium molybdate tetrahydrate and thiourea. More preferably, the molar mass ratio of ammonium molybdate tetrahydrate to thiourea is 1:20-30.
[0011] More preferably, the preparation method of molybdenum disulfide is: dissolving ammonium molybdate tetrahydrate and thiourea in water, heating to 220° C. and keeping warm for 13-15 hours, washing with water and ethanol after cooling, and vacuum drying to obtain the molybdenum disulfide.
[0012] The inventors have found that when graphite is used in combination with molybdenum disulfide, it not only has an excellent lubricating effect, but also can improve the stability and durability of the lubricating coating, and can still maintain good lubrication performance under high temperature conditions. This may be because when graphite and molybdenum disulfide are used together, on the one hand, the presence of graphite can inhibit the agglomeration of molybdenum disulfide, and on the other hand, the two form a uniform continuous phase, and a sandwich-like bonding structure of covalent bond / ionic bond / covalent bond is formed between graphite and molybdenum disulfide, which can effectively prevent chemical reactions and improve lubricity; and graphite protects molybdenum disulfide, reducing its oxidation failure phenomenon, thereby enhancing the stability and durability of the coating. Especially when the average particle size of graphite is less than 3um and the specific surface area is 10-50m 2 / g, combined with specific nano molybdenum disulfide, the lubrication effect, stability and durability are significantly improved. The inventors analyzed that it may be due to the use of excessive thiourea in the preparation of nano molybdenum disulfide. The presence of thiourea inhibits the self-assembly of molybdenum disulfide to a certain extent, so that there are more active points in its molecular layer, thereby making it more strongly bonded with graphite, forming more heterogeneous interfaces, and a large number of heterogeneous interfaces can significantly reduce the friction coefficient, improve lubrication performance, and inhibit the structural decay of graphite and molybdenum disulfide during the friction process under friction conditions; at the same time, it can also provide better protection for molybdenum disulfide.
[0013] Preferably, the average particle size of the molybdenum carbide is 1-20 μm, and the specific surface area is 1-50 m 2 / g.
[0014] Preferably, the raw material of the lubricating coating further contains carbon black, and the mass ratio of the carbon black to molybdenum disulfide is 1:3-5.
[0015] More preferably, the carbon black has a particle size of 1-200 nm and a resistivity of <1 Ohm·m.
[0016] The present invention also contains carbon black with a particle size of 1-200nm. The inventors have found that the addition of carbon black can further better protect materials such as molybdenum disulfide. Carbon black with a particle size of 1-200nm can be better dispersed in the material system of the present invention, and has a coating and protection effect on materials such as molybdenum disulfide. The nano molybdenum disulfide of the present invention, with an average particle size of less than 3um and a specific surface area of 10-50m 2 / g of graphite and 1-200nm of carbon black are used together, especially when the lubricating coating is sprayed on the surface of the wire by electrostatic spraying, the coating is very uniform. However, the carbon black should not be too much, otherwise it will affect the lubrication effect of the coating, and the coating uniformity will deteriorate. It may be because the excessive carbon black will self-aggregate, and its combination with molybdenum disulfide will affect the layered structure between graphite and molybdenum disulfide, thereby affecting the lubrication effect and spraying uniformity.
[0017] Preferably, the silicate is a mixture of one or more of sodium silicate, magnesium silicate, aluminum silicate, potassium silicate and lithium silicate.
[0018] In order to make the lubricating coating maintain excellent adhesion and lubrication effect at high temperature, preferably, the silicate is sodium silicate or magnesium silicate. More preferably, the mass ratio of sodium silicate to magnesium silicate is 3-5:1.
[0019] More preferably, the modulus of the sodium silicate is 1-2.5.
[0020] Preferably, the particle size of the silicon powder is 1-100 um.
[0021] Preferably, the diluent is one or a mixture of polyethylene glycol, xylene, acetone, butyl acetate, isoamyl acetate, ethylene glycol ethyl ether acetate, ethylene glycol butyl ether acetate, and octadecyl acrylate.
[0022] In order to make the components in the system disperse more evenly and enhance the uniformity of the lubricating coating during coating, preferably, the diluent is ethylene glycol butyl ether acetate and octadecyl acrylate. More preferably, the mass ratio of ethylene glycol butyl ether acetate to the octadecyl acrylate is 5-8:1.
[0023] Another aspect of the present invention provides a method for preparing a high temperature resistant and high lubricity coating for aviation fastener wire, the specific steps of which are as follows: adding graphite, molybdenum disulfide, molybdenum carbide, silicon powder and carbon black into water and stirring evenly, then adding silicate and diluent and stirring evenly to obtain the coating.
[0024] The third aspect of the present invention provides an application of a high temperature resistant and highly lubricating coating in aviation fastener wires. In the processing of aviation fastener wires, the lubricating coating can effectively protect the material, reduce friction, provide lubrication protection, and inhibit adhesive wear.
[0025] The lubricating coating of the present invention is coated on the surface of the wire material with a thickness of 4-8 um.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] In the present invention, by using graphite, molybdenum disulfide and other materials in a specific proportion, the raw materials work together to obtain a lubricating coating with excellent high temperature resistance and high lubrication effects. The coating not only has a good bonding effect at room temperature, but also maintains excellent bonding force and good lubricity at high temperatures. The coated sample wire is kept in an oven (temperature 850°C) for 2 minutes and then taken out for inspection. The coating is intact and there is no discoloration or peeling. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A sample of the titanium alloy wire coated with the coating according to Example 1 of the present invention;
[0029] Figure 2 The titanium alloy wire before being coated with the coating according to Example 1 of the present invention;
[0030] Figure 3 The titanium alloy wire product after being coated with the coating according to Example 1 of the present invention;
[0031] Figure 4 This is a morphology diagram of the coating on the surface of the titanium alloy wire after being coated with the coating of Example 1 of the present invention;
[0032] Figure 5This is a wire sample diagram of a qualified sample after the isolation and friction performance tests of the coating in Example 1 of the present invention;
[0033] Figure 6 This is a wire sample diagram of an unqualified sample after the isolation and friction performance tests of the coating of comparative example 3 of the present invention;
[0034] Figure 7 This is a morphology diagram of a wire sample after thermal stability testing of the coating in Example 1 of the present invention;
[0035] Figure 8 This is a morphology diagram of a wire sample after thermal stability testing of the coating of Comparative Example 2 of the present invention;
[0036] Fig. 9 This is a morphology diagram of a wire sample after thermal stability testing of the coating of Comparative Example 6 of the present invention;
[0037] Fig.10 A two-die two-punch continuous pier specimen for testing the lubrication effect of the coating according to Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other without conflict.
[0039] Example
[0040] Examples 1-5 and Comparative Examples 1-6 of the present invention all provide a high temperature resistant and highly lubricating coating for aviation fastener wires, wherein the raw materials of the coating include: graphite, molybdenum disulfide, molybdenum carbide, carbon black, silicate, and a diluent. The weight parts of the raw material components of Examples 1-5 and Comparative Examples 1-6 are shown in Table 1.
[0041] On the other hand, an embodiment of the present invention provides a method for preparing a high-temperature resistant and high-lubricity coating for aviation fastener wire, and the specific steps are as follows: adding graphite, molybdenum disulfide, molybdenum carbide, silicon powder, and carbon black to 100 parts by weight of water and stirring evenly, then adding silicate and diluent, and stirring at 3000r / min for 5h to obtain the coating.
[0042] Among them, the average particle size of graphite is 1um and the specific surface area is 18.98m 2 / g, purity> 99.9%, purchased from Bohuasi Nanotechnology Co., Ltd.; the average particle size of molybdenum carbide is 2nm, and the specific surface area is 10m 2 / g, purity is 99.9%, volume density is 1.8g / cm 3 , purchased from Beijing Yijin New Materials Technology Co., Ltd. The average particle size of carbon black is 40nm, the resistivity is <0.8Ohm·m, purchased from Tianjin Huayuan Chemical Technology Co., Ltd. The modulus of sodium silicate is 1.03±0.03, analytical grade, purchased from Hengxing Fine Chemical Co., Ltd. The average particle size of magnesium silicate is 60-100 mesh, purchased from Shanghai McLean Biochemical Technology Co., Ltd. The average particle size of silicon powder is 20um, purchased from Lianyungang Haosen Mineral Products Co., Ltd. The CAS number of ethylene glycol butyl ether acetate is 112-07-2; the CAS number of octadecyl acrylate is 4813-57-4.
[0043] The preparation method of molybdenum disulfide is as follows: dissolve 2 mmol of ammonium molybdate tetrahydrate (CAS No. 12054-85-2) and 50 mmol of thiourea (CAS No. 62-56-6) in 60 mL of deionized water, heat to 220° C. and keep warm for 14 hours, wash with water and ethanol after cooling, and vacuum dry at 60° C. for 12 hours to obtain the product.
[0044] Table 1
[0045]
[0046]
[0047] Comparative Example 7
[0048] This embodiment provides a high temperature resistant and high lubricity coating for aviation fastener wire. The specific implementation method is the same as that of Example 1. The difference from Example 1 is that the particle size of the molybdenum disulfide is 1000 nm and is purchased from Shanghai Lianghan Nano Technology Co., Ltd.
[0049] Comparative Example 8
[0050] This embodiment provides a high temperature resistant and high lubricity coating for aviation fastener wire. The specific implementation is the same as that of Example 1. The resistivity of the carbon black is <1.5 Ohm·m and is purchased from Tianjin Huayuan Chemical Technology Co., Ltd.
[0051] Performance Testing
[0052] 1. Coating curing effect test:
[0053] The coatings of Examples 1-5 were applied to The curing effect test was carried out on the surface of titanium alloy wire. The initial drying temperature of the material was 80-120℃, the curing temperature was 250℃, and the curing time was 10-15min. The coating on the surface of the wire was dense and complete, black and gray in color, and there was no residue when touched by hand.
[0054] 2. Isolation and friction performance test of coating:
[0055] The sample silks of Examples 1-5 and Comparative Examples 1-8 were cleaned, sent to an electrostatic spray box, sprayed with the prepared coating, and then sent to an oven for coating curing.
[0056] Test method: The coatings of Examples 1-5 and Comparative Examples 1-8 were applied to the The titanium alloy wire surface is coated with a thickness of 4-8um. The coated wire samples of Examples 1-5 and Comparative Examples 1-8 are directly drawn using an eye mold with a diameter reduction rate of about 10%. If the wire samples can pass the drawing smoothly and the surface coating of the wire samples is intact, it is qualified. After drawing, the surface coating of the wire samples is considered unqualified if it falls off, whitens, or is scratched. The isolation and friction performance results are shown in Table 2 below.
[0057] 3. Thermal stability test:
[0058] Test method: The coatings of Examples 1-5 and Comparative Examples 1-8 were applied to the The surface of the titanium alloy wire is coated with a thickness of 4-8um. The coated wire is kept in an oven (temperature 850℃) for 2 minutes and then taken out for inspection to see if the coating is intact and has no discoloration or peeling. If the coating is intact and has no discoloration or peeling, it is recorded as Class A, if the coating has slight discoloration or peeling, it is recorded as Class B, and if the coating has a lot of discoloration or peeling, it is recorded as Class C. The test results are shown in Table 2.
[0059] 4. Adhesion test:
[0060] Test method: Use QFD electric paint film adhesion tester to test the adhesion of the coating according to GB / T 1720-1979 (1989).
[0061] The coatings of Examples 1-5 and Comparative Examples 1-8 were subjected to adhesion tests, and the adhesion grades were measured as shown in Table 2 below.
[0062] 5. Lubrication effect test:
[0063] The coatings of Examples 1-5 and Comparative Examples 1-8 were applied to the The surface of the titanium alloy wire is coated with a thickness of 4-8um. The wire is passed through a continuous hot forging of two dies and two punches, with a heating temperature of 750℃, and the material forming condition is observed. If there is no coating damage and shedding, material sticking to the mold, splitting, etc., the product is considered qualified, otherwise the product is unqualified. The results of the product qualification are shown in Table 2 below.
[0064] Table 2
[0065]
Claims
1. A high temperature resistant and highly lubricating coating for aviation fastener wire, characterized in that: The raw materials of the coating include, by weight: 20-30 parts of graphite, 30-40 parts of molybdenum disulfide, 3-10 parts of molybdenum carbide, 20-30 parts of silicate, 1-5 parts of silicon powder, and 15-30 parts of diluent; The average particle size of the graphite is less than 3 μm, and the specific surface area is 10-50 m 2 / g; The molybdenum disulfide is nano molybdenum disulfide; the raw materials for preparing the molybdenum disulfide include: ammonium molybdate tetrahydrate and thiourea; the molar mass ratio of the ammonium molybdate tetrahydrate to thiourea is 1:20-30; The raw material of the lubricating coating further contains carbon black; the mass ratio of the carbon black to molybdenum disulfide is 1:3-5; The silicate is sodium silicate and magnesium silicate; the mass ratio of sodium silicate to magnesium silicate is 3-5:1; The diluent is ethylene glycol butyl ether acetate and octadecyl acrylate; the mass ratio of ethylene glycol butyl ether acetate to octadecyl acrylate is 5-8:1; The particle size of the carbon black is 1-200 nm, and the resistivity is less than 1 Ohm·m; The fastener is a titanium alloy fastener.
2. Application of the high temperature resistant and high lubricity coating according to claim 1 in aviation fastener wire.
Citation Information
Patent Citations
Coating material for substrates, containing a lubricant for shaping processes
WO2007076769A2
Cited By
Multi-phase ceramic composite strengthened wear-resistant coating on surface of tc6 titanium alloy and preparation method thereof
CN122751118A